Because of Winn-Dixie / Chomps - Wang, Wayne, 1949-; Daniels, Jeff, 1955-; Tyson, Cicely; Matthews, Dave, 1967-; Saint, Eva Marie, 1924-; Robb, AnnaSophia, 1993-; Lindenlaub, Karl Walter; Portman, Rachel; DiCamillo, Kate.; Twentieth Century Fox Home Entertainment, Inc. ([Beverly Hills, Calif.] : 20th Century Fox Home Entertainment, 2005)
The heartwarming 'tail' of a young girl whose life is changed by a scruffy, fun-loving pooch she names Winn- Dixie. The special bond between them works magic on her reserved dad and the eccentric townspeople they meet during one unforgettable summer.
Originally produced as a motion picture in 2005.
Based on the novel by Kate DiCamillo.
Special features: Family sizzle trailer (Sandlot 2, Garfield, Fat Albert, Robots); scene specific commentary by Anna Sophia Robb; behind the scenes with Winn Dixie (epk featurette); music soundtrack promo; inside look; Ice age 2; commentary by Jeff Daniels and Trevor Albert; gag reel; Diamond in the ruff featurette.
Director of photography, Karl Walter Lindenlaub ; editor, Deirdre Slevin ; music, Rachel Portman ; costume designer, Hope Hanafin ; production designer, Donald Graham Burt.
Jeff Daniels, Cicely Tyson, Dave Matthews, Eva Marie Saint, Annasophia Robb, Elle Fanning, Courtney Jines, Nick Price, Luke Benward, Marca Price.
MPAA rating: PG; for thematic elements and brief mild language.
Keywords: Dogs -- Juvenile films; City and town life -- Juvenile films; Friendship -- Juvenile films; Feature films; Children's films